(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Lipoprotein monitoring is desirable in the management of medical conditions such as atherosclerotic cardiovascular disease and coronary artery disease, in which controlling the concentration of these chylomicrons is crucial. Current clinical methods are complex and present poor reproducibility between laboratories. For these reasons, recent guidelines discard the assessment of low-density lipoprotein cholesterol (LDL-C) as a routine analysis during lipid-lowering therapies. Concerning the importance of monitoring this parameter, the authors present an electrochemical immunosensor constructed from a simple and easy-to-reproduce platform that allows detecting and quantifying LDL nanoparticles directly from human serum samples. The performance of the biosensor was studied by scanning electron microscopy, cyclic voltammetry, and electrochemical impedance spectroscopy. The biosensing platform displays good stability and linearity between 30 mg dL-1 and 135 mg dL-1 with a detection limit of 20 mg dL-1. The proposed biosensor can be easily employed for monitoring LDL concentration in clinical treatments.